Rendimiento y composición corporal de cuyes (cavia porcellus) suplementados con tres niveles de harina de sangre bovino (bos taurus) procesada artesanalmente - Zamora Huamán, Segundo José (2016)
This research aimed to evaluate the performance and body composition of Guinea pigs (Cavia porcellus) supplemented with three levels of bovine blood meal (Bos taurus) processed by hand in Small Animals Module of Chachapoyas Experimental Station of the Toribio Rodríguez of Mendoza of Amazonas National University. Food rations were evaluated in an iso energy and iso protein levels with 4%, 8% and 12% of blood meal, using 36 Guinea Pigs weaned males of 21 days of age, divided into groups of 9 animals per treatment; all treatments were fed with forage maize in a milky state and a mix of grains . Assessed parameters such as dry matter, weight gain, feed conversion, housing performance, percentage of body fat and economic evaluation. Gains weight, dry matter, feed conversion and body composition had no significant differences (p > 0.05), but in the economic evaluation animals treated with higher content of blood in their ration meal decreased the total costs compared with the control. It is concluded that the addition of 12% bloodmeal lowers costs without affecting meat quality and production indicators.